Legionella pneumophila Infection Rewires the Acanthamoeba castellanii Transcriptome, Highlighting a Class of Sirtuin Genes - Li, Pengfei; Vassiliadis, Dane; Ong, Sze Ying; Bennett-Wood, Vicki; Sugimoto, Chihiro; Yamagishi, Junya; Hartland, Elizabeth L.; Pasricha, Shivani (Frontiers in Cellular and Infection Microbiology, 2020)
Legionella pneumophila is an environmental bacterium that has evolved to survive predation by soil and water amoebae such as Acanthamoeba castellanii, and this has inadvertently led to the ability of L. pneumophila to survive and replicate in human cells. L. pneumophila causes Legionnaire's Disease, with human exposure occurring via the inhalation of water aerosols containing both amoebae and the bacteria. These aerosols originate from aquatic biofilms found in artifical water sources, such as air-conditioning cooling towers and humidifiers. In these man-made environments, A. castellanii supports L. pneumophila intracellular replication, thereby promoting persistence and dissemination of the bacteria and providing protection from external stress. Despite this close evolutionary relationship, very little is known about how A. castellanii responds to L. pneumophila infection. In this study, we examined the global transcriptional response of A. castellanii to L. pneumophila infection. We compared A. castellanii infected with wild type L. pneumophila to A. castellanii infected with an isogenic ΔdotA mutant strain, which is unable to replicate intracellularly. We showed that A. castellanii underwent clear morphological and transcriptional rewiring over the course of L. pneumophila infection. Through improved annotation of the A. castellanii genome, we determined that these transcriptional changes primarily involved biological processes utilizing small GTPases, including cellular transport, signaling, metabolism and replication. In addition, a number of sirtuin-encoding genes in A. castellanii were found to be conserved and upregulated during L. pneumophila infection. Silencing of sirtuin gene, sir6f (ACA1_153540) resulted in the inhibition of A. castellanii cell proliferation during infection and reduced L. pneumophila replication. Overall our findings identified several biological pathways in amoebae that may support L. pneumophila replication and A. castellanii proliferation in environmental conditions.